Growth Model of Pine (Pinus merkusii Jungh. Et de Vriese) Stand on Community Forest in Tana Toraja Regency - Melewanto Patabang; Daud Malamassam; Hardjanto H (Institut Pertanian Bogor (IPB University), 2014)
Growth modeling and yield simulation of forest is a very important aspect in forest management including community forests. Stand growth model is an abstraction of the dynamic nature of a forest stand, including growth, ingrowths, mortality, and other changes in the structure and composition of the stand. In forest management, growth estimation plays an important role in supporting the sustainability of the benefits value of the community forests. The objectives of the research were to find out the stand growth model and the potential of community's pine forest. The study was conducted at the location of the community pine forests in District Mengkendek Tana Toraja Regency. Sample location, as representative of stand age classes that distribute on some villages in Mengkendek District, were selected by purposive sampling.The study results indicate that the most suitable model for upper trees mean height (H) is Weibull Model, for growth diameter and growth volume is Logistic Model . The stand mean height (h) can be presented as a function of H and Relative Spacing Ratio (Sr) on the basis of function log Sr = 0,197 – 0,653 log H, then the tree volume, can be estimated on the basis of function log V = -1,70 + 0,94logD + 1,50logh, and then the growth function of volume on the basis of function V = 1.008 / 1 + 251.322 exp(-0.373t. Further, the maximum value of stand Annual Increment was 18 m3ha-1year-1, attained at the age of 20 years.